New distribution record of two pen shells (Bivalvia : Pinnidae) from the Seagrass Beds of Sg. Pulai, Johore Malaysia - Idris, Mohd Hanafi; Arshad, Aziz; Bujang, Japar Sidik; Daud, Siti Khalijah; Abdul Ghaffar, Mazlan (2008)
Studies on taxonomy of pen shells were conducted at Merambong Shoal (N1° 19’ 55.62? E103° 35’ 57.75? ), Tanjung Adang Shoal (N1° 19’ 48.03? E103° 33’ 59.44? ) and Merambong Island (N1° 18’ 54.83? E103° 36’ 33.37? ) off South Western Johor coast, Peninsular Malaysia from August 2005 to June 2006. One hundred and seven individuals of pen shells were collected from the study areas for taxonomy identification. Pen shells were grouped based on the internal and external surface of the valves. Seven species were clearly identified where Atrina and Pinna are dominant. Among these seven species, "Pinna deltodes (Menke, 1843) and Pinna incurva (Gmelin, 1791)" are the new distribution record from the seagrasses bed of Sungai Pulai.